Analysis of Maternal Health in Local Area Monitoring-Maternal and Child Health (LAM-MCH) Indicators in Pagerageung Health Center - Danefi, Tupriliany; Susanti , Santi (KIAN JOURNAL, 2023)
Objective: The purpose of this research is to know the description of the results of the analysis of maternal health in the indicators of LAM-MCH  in Sukamaju Village, the Working Area of ​​the Pagerageung Health Center, Tasikmalaya Regency, in 2022.   Methods: The research method used is a descriptive method. Data analysis used with univariate analysis. Results: The results showed that the coverage indicator for K1 visits was 87.08%, the coverage indicator for K4 visits was 78.20%, the coverage indicator for delivery by health personnel was 87.51%, the coverage indicator for postpartum visits was 87.51%, the achievement coverage indicator Early detection of risk factors and complications of obstetrics by health workers and the public at 26.66% Conclusion: The conclusion of this study is that indicators of maternal health have not been achieved, especially coverage of K1, K4, delivery of health workers, postpartum visits and handling of obstetric complications cases. Suggestions for this research are the need for mutually supportive cooperation between pregnant women, midwives (health workers), and also the community or regional cadres.